Respuesta :
The correct result would be y = -6/5 - (2 * sqrt(6))/5 and y = (2 * sqrt(6))/5 - 6/5.
For this case we have the following quadratic expression:
[tex] (5y + 6) ^ 2 = 24
[/tex]
From here, we must clear the value of y.
For this, we follow the following steps:
1) We clear the square term:
[tex] (5y + 6) =+/-\sqrt{24} [/tex]
[tex] (5y + 6) =+/-2\sqrt{6} [/tex]
2) Pass the value of 6 by subtracting:
[tex] 5y =-6+/-2\sqrt{6} [/tex]
3) Pass the value of 5 to divide:
[tex] y =\frac{-6+/-2\sqrt{6} }{5} [/tex]
Answer:
The solutions to the quadratic equation are:
[tex] y =\frac{-6+2\sqrt{6} }{5} [/tex]
[tex] y =\frac{-6-2\sqrt{6} }{5} [/tex]